Efforts to Improve Public Awareness of the Environment through Empowerment-Based CSR Program Activities (Case Study: Donan Village, Cilacap Regency): Upaya Peningkatan Kesadaran Masyarakat terhadap Lingkungan melalui Kegiatan Program (CSR) Berbasis Pemberdayaan (Studi Kasus: Kelurahan Donan, Kabupaten Cilacap) - Shodikin, King Amil Hamzah Al Hakim (RADIANT: Journal of Applied, Social, and Education Studies, 2024)
Efforts to increase public awareness of the environment can be done through various programs, one of which is through the Corporate Social Responsibility (CSR) program. The implementation of the CSR program can be seen in RW 14, Donan Village, Central Cilacap District, Cilacap Regency. This area is close to the oil and gas company, PT Kilang Pertamina Internasional RU IV Cilacap. This study was conducted to reveal the efforts made by the company to increase public awareness of the surrounding environment. Through field observations and stakeholder interviews. The results of this study mapped efforts to increase public awareness carried out in several strategic ways including: 1) Creating a Comfortable Environment with the Proklim concept, 2) Optimizing the Role of KWT towards Food Self-Sufficiency, 3) Creating a strong, creative and productive young generation, and 4) Increasing and optimizing the Role of Social Capital. The impact of the program on the Environment of RW 14, Donan Village can create changes in behavior and mindset of the community, especially in sustainable environmental management within the family. Previously, people did not care about waste management and efforts to create food security for families, but now people have various kinds of environmentally conscious social activities.